Fatigue testing and analysis of results - Weibull, Waloddi, 1887-1979 (Published for Advisory Group for Aeronautical Research and development, North Atlantic Treaty Organization, by Pergamon Press, 1961)
Fatigue Testing and Analysis of Results discusses fundamental concepts of fatigue testing and results analysis. The book begins with a description of the symbols and nomenclature selected for the present book, mainly those proposed by the ASTM Committee E-9 on Fatigue. Fatigue testing methods are then discussed including routine tests, short-life and long-life tests, cumulative-damage tests, and abbreviated and accelerated tests. Separate chapters cover fatigue testing machines and equipment; instruments and measuring devices; and test pieces used in fatigue testing. The factors affecting tes.